The Effectiveness Of The Application Of The Last Resort Principle On Child Residivists In The Child Criminal Justice System - Mahdiyyah; Muchtar, Syamsuddin; Mirzana, Hijrah Adhyanti (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2022)
Improper criminal imposition can ignore child protection arrangements, because child punishment should be the last resort or the last resort principle and imposed only for a short time. The method used in this research is empirical legal research. Empirical legal research is legal research conducted by examining primary data, namely data obtained directly from the community. As for the results of the Guidance Program for Correctional Students at the Class II Maros Special Child Guidance Institute, there are still some shortcomings such as the absence of a legal awareness program and the provision of formal education which indirectly affects the non-fulfillment of the rights of correctional students, especially because there are still adult prisoners who should be separated from children. The actual role of the officers of the Child Special Guidance Institution in its implementation is still not optimal due to the lack of quality and human resources, and there is no special coach for children. Keywords: Child Crime; Effectiveness; Recidivists